Profitability, investment and employment - a survey of recent developments in medium-term growth theory - Barry, Frank G. (Economic & Social Studies, 1986)
This paper reviews the recent theoretical literature on the relationship between profitability, investment and employment in an attempt to clarify the roles of demand-management, supply-management and incomes policies in stimulating employment and growth.
Keywords: Employment; Economic growth